Preparation and characterization of nanostructured CuO thin films using spray pyrolysis technique - Moumen, Abderrahim; Hartiti, Bouchaib; Comini, Elisabetta; El khalidi, Zahira; Arachchige, Hashitha M.M. Munasinghe; Fadili, Salah; Thevenin, Philippe (Superlattices and microstructures, 2019)
In this work, the suitability of CuO thin films on gas sensors and solar cells applications was investigated. CuO thin films were deposited using spray pyrolysis. The effect of substrates temperature on the films structural and optical properties was discussed. X-ray diffraction showed the appearance of tenorite phase of cupric oxide CuO without impurities indicating the formation of pure cupric oxide material. Raman spectroscopy confirmed the results obtained in XRD and showed CuO phase formation. A crystallinity improvement was measured increasing the temperature from 300 °C to 375 °C. Optical properties such as band gap energy, refractive index, extinction coefficient and optical conductivity were extracted using transmittance/absorbance data giving by UV-Visible spectrophotometer. Low transmittance, high absorbance and small band gap energy were observed at the highest substrate temperature, these characteristics make CuO an appropriate material to be used as absorber layer in photovoltaic applications. The performances of CuO thin film for acetone sensing were proved: 33% of response, 160 s and 360 s as response and recovery time, respectively. •The fabricated CuO films are applicable in gas sensors and photovoltaic.•CuO is a good absorber layer in photovoltaic applications.•The response, response/recovery time of CuO were studied.